Biomechanical differences between left- and right-handed baseball pitchers - Solomito, M. J.; Ferreira, J. V.; Nissen, C. W. (Sports Biomechanics, 2017)
Left-handed baseball pitchers are thought to have a number of theoretical advantages compared to right-handed pitchers; however, there is limited scientific research detailing differences in the pitching mechanics of right- and left-handed pitchers. Therefore, this study sought to understand whether any kinematic and kinetic differences existed between right- and left-handed baseball pitchers. A total of 52 collegiate pitchers were included in this study; 26 left-handed pitchers were compared to 26 age-, height-, weight- and ball velocity-matched right-handed pitchers. Demographic information, passive shoulder range of motion and kinematic and kinetic data were obtained for each pitcher participating in the study. Results indicated that left-handed pitchers did not have a glenohumeral internal rotation deficit as compared to right-handed pitchers. Kinematic analysis indicated that elbow flexion, horizontal glenohumeral abduction and wrist coronal plane motion were significantly different between the two study cohorts. It was also noted that left-handed pitchers had increased elbow varus moments. The findings of this study suggest that pitching coaches should be aware that there are biomechanical differences between left- and right-handed pitchers. ABSTRACT FROM AUTHOR